Comparison between two conical induction machines designed for an electric vehicle application - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
This study focuses on the comparison between two conical machines designed for an electrical-vehicle application. An optimal case, with an optimal cone angle, is compared to a worst-case scenario where the tapering is increased up to the maximum allowed dimensions. Simulations show that when the cone angle is not appropriately chosen the advantages that a tapered motor can offer over a classical cylindrical machine can be lost. In order to show the worsening effects of a not well pondered cone angle choice, a prototype of the conical machine with the largest conical dimensions has been built. The results obtained using finite element models (FEM) have been confirmed through experimental tests demonstrating the validity of the numerical analyses. © 2019 IEEE.
Keywords: Electric vehicle; In-wheel motor; Induction motor; Tapered rotor geometry; Traction motor